118: Assessing the Child Health Information Needs of Parents and Families. Issue 6 (1st June 2014) - Ramadan, K; Fridman, M; Ford-Jones, L; Mistry, N; Nichols, N
Abstract: BACKGROUND: Parents seek child health information for dealing with acute illnesses, guidance on parenting, and to improve knowledge of child development. There are many comprehensive child health information sources available; however, no centralized access point exists making navigation a challenge for many parents. Well-defined barriers include access, language, appraisal of information sources, and health literacy. OBJECTIVES: This study aimed to determine the health knowledge needs, information resources, and barriers to access among families with well children aged zero to 12 years who are seeking preventative or proactive health knowledge information. DESIGN/METHODS: Ethics approval was obtained from our institutional Quality Improvement Projects review board. Six focus groups were conducted with parents of children aged zero to 12 years from various racial and socioeconomic backgrounds. Focus groups were recorded and transcribed using a professional transcription service. Data analysis involved thematic coding of transcripts. Data triangulation was achieved by having multiple investigators code the first focus group to develop, through a consensus-building approach, a series of general themes that were explored across data sets. This model was refined using the subsequent focus group data. Major themes and sub-themes were determined by analyzing trends and patterns. RESULTS: Analysis yielded four major themes: sources for health information, information autonomy, insecurity, and barriers. Major sources of health information included the internet, physicians, and help lines. Information autonomy referred to parents' ability to make decisions and obtain information without health care assistance. Insecurity referred to acute or chronic stress associated with child health and wellness issues. Barriers referred to social and health care related difficulties in accessing information. A central theme, empowerment, was found to link all major themes. Empowerment referred to parents' ability to be successfully involved in the care of their child in terms of information seeking, investigation and maintaining general well-being. A subgroup of parents were unempowered and described a lack of information autonomy, a higher level of insecurity and more varied and severe barriers in caring for their children. Parents expressed a desire for a resource that is broadly accessible, interactive, personalizable, credible, up to date, and intuitive. CONCLUSIONS: In a subgroup of unempowered parents, it may not be adequate to give specific information for discrete issues as this may perpetuate reliance. The goal of child health information resource development should be to produce a system that will empower all parents and provide the tools and resources for parents to search for information autonomously and effectively.